KAJIAN FAKTOR-FAKTOR YANG MEMPENGARUHI PENUMPUKAN PENYERAPAN ANGGARAN DI AKHIR TAHUN (STUDI DI KOTA PEKALONGAN TAHUN 2013) (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of this research is to find out factors influencing accumulation of budget absorption in the end of 2013 in government of the City of Pekalongan. The type of research used is qualitative and quantitative descriptive. The research of qualitative descriptive is used to see the view of budget absorption in government of the city of Pekalongan in the year of 2013, whether it is absorbed optimally or getting a delay of absorption and then it accumulates. While qualitative descriptive is a research activity to provide the view of Budget Planning Factor (X1), Budget Applying Factor (X2), internal factor of work unit (X3), Human Resources Factor (SDM) (X4), Document Factor (X5), and Administration Factor (X6) towardsaccumulation of budget absorption in the end of year (Y). Samples used are 81 SKPD located in government of the city of Pekalongan, namely Budget User Officer, Financial Management Officer, Technically Financial Applying Officer and Expenditure Treasurer. The type of data used in this research is primary and secondary data. While the tool of statistical analysis used is test of validity with the technique of factor analysis, test of reliability with technique of cronbach’s alpha, multi linear regression and test of classical assumptions including normallity, multicollinearity and heteroscedasticity. The result of research indicates that the items of question for every independent (X) and dependent (Y) variable has met a requirement of validity. This is seen from value of loading factorwhich is more than 0.40, and value of KMO is more than 0.50. Reliability value of cronbach’s alpha has been more than 0.60. While the result of regression analysis also indicates that it has been met a requirement of classical assumptions, namely there is no multicollinearity and heteroscedasticity, and has been distributed normally. Based on the influence simultaneously (F Test), independent variable including Budget Planning Factor (X1), Budget Applying Factor (X2), Internal Factor of work unit (X3), Human Resources Factor (SDM) (X4), Document Factor (X5), and Administration Factor (X6) have a significant influence towards accumulation of budget absorption in the end of year (Y) of 2013 in government of the city of Pekalongan. Partially, variable influenced significantly towards accumulation of budget absorption is only human resources factor variable and document variable, while the others are not significant on it. Value of R square is 45.8%, while the rest is 54.2% explained by other independent variables besides independent variable used. Key words :   Factors Influencing Accumulation of Budget Absorption